Turkey and Saudi Arabia Relations in the Twenty-First Century: Power, State Identity and Religion - Ozturk, Ahmet Erdi (Border Crossing, 2022)
During the first two decades of the Twenty-First century, we have begun — and will continue to — experience a new dimension in the political roles of power, state identity and religion in different ways. One can read this situation as the concentration of these notions at the core of global politics implemented by political leaders who have been transforming their countries appearances and perceptions worldwide. Furthermore, we will also be experiencing an increase in the intersectionality between domestic and foreign policy that are covered by power, state identity and religion. Within this framework, Muslim majority countries in the Middle East, which are underdeveloped in terms of liberal democracy, have been engaging in a global struggle over state identity and power that stretches from different part of the world, and this has been affecting both the regional dynamics and beyond via global Muslim diasporas. Among many different examples two of these countries have become quite visible: Turkey, under the leadership of Recep Tayyip Erdogan, and Saudi Arabia with its crown prince, Mohammed bin Salman. The two countries have long been in a problematic relation and this has been intensified after Saudi agents murdered journalist Jamal Khashoggi at the kingdom's Istanbul consulate in 2018. But, how did their relations come to this point and how do power, state identity and religion play different roles? To answer this question, this article argues that not directly religion, but also international power struggles and differences between state identities could play different roles into the relations between states, but the positions of the states could not be stable and can be changeable according to their interests.